MISKONSEPSI MEMBANDINGKAN PECAHAN BERPENYEBUT BERBEDA DI KELAS 5 SEKOLAH DASAR - Agie Nurwati; Hepsi Nindiasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Misconceptions in mathematical concepts can significantly hinder students' learning processes, especially in foundational topics such as fractions. This study aims to identify and analyze common misconceptions encountered by 5th-grade elementary school students when comparing fractions with different denominators. The research employs a qualitative descriptive method, targeting students from SD Negeri Serang 16 who experience difficulties in this area. Data collection techniques include problem-solving tests and interviews to understand students' reasoning. Findings indicate that students often assume larger denominators signify larger fractions, directly compare numerators or denominators without adjusting the fractions, or incorrectly apply methods to find equivalent fractions. Additionally, challenges in converting mixed numbers into improper fractions exacerbate these misconceptions. The study highlights the need for visual and contextual teaching aids, such as fraction bars or real-life examples, to reinforce students' conceptual understanding. Implementing innovative teaching models and emphasizing mastery of prerequisite knowledge, such as multiplication and least common multiples, are suggested as strategies to address these issues. By addressing these misconceptions, educators can enhance students' comprehension of fractions, laying a stronger foundation for future mathematical learning.